2010
DOI: 10.1021/jp911856q
|View full text |Cite
|
Sign up to set email alerts
|

Fischer−Tropsch Synthesis: An In-Situ TPR-EXAFS/XANES Investigation of the Influence of Group I Alkali Promoters on the Local Atomic and Electronic Structure of Carburized Iron/Silica Catalysts

Abstract: The promoting impact of alkali metals (i.e., Li, Na, K, Rb, Cs) on the carburization rate of Fe in Fe/Si catalysts was investigated by X-ray absorption spectroscopy. A multisample holder was used, allowing nearly simultaneous examination of the catalysts during activation in a CO/He mixture. With the white line intensity and shape as a fingerprint for oxidation state, TPR/XANES analysis enabled us to measure the relative composition of the different compounds as a function of the carburization time, temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
129
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 29 publications
11
129
0
Order By: Relevance
“…These peaks are associated with reduction of Fe 2 O 3 to lower oxides (i.e., Fe 3 O 4 and defect-laden form of this oxide) prior to carburization. The peaks are fully consistent with our previous CO-TPR XANES/EXAFS studies [33][34][35]. The second peak is located in the temperature range of 350-525°C.…”
Section: Resultssupporting
confidence: 90%
“…These peaks are associated with reduction of Fe 2 O 3 to lower oxides (i.e., Fe 3 O 4 and defect-laden form of this oxide) prior to carburization. The peaks are fully consistent with our previous CO-TPR XANES/EXAFS studies [33][34][35]. The second peak is located in the temperature range of 350-525°C.…”
Section: Resultssupporting
confidence: 90%
“…In this sense, the alkali promoter shifts the hydrocarbon selectivity towards longer chain hydrocarbons and olefin products. 6 Furthermore, it has been reported that such alkali elements (Na, K or Cs) are electronic promoters that transfer part of their electron density to Ru even in its oxidized state, which strengthens the CO-metal interaction whereas weakening the C-O bond. 4,[7][8][9] Recently, some experimental evidences of the partial reduction of Cs in Cs-Ru/C catalysts during temperatureprogrammed reduction have been provided by X-ray absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Promotion effect of alkali metals has attracted continuous interests for several decades in heterogeneous catalysis [1][2][3], such as in Fischer-Tropsch synthesis (FTS) [4,5], ammonia synthesis [6], steam reforming of methane [7], low alcohol synthesis [8] and epoxidation reaction [9]. Although many studies focused on promotion effect of alkali metals on metal surfaces [10][11][12], the mechanisms in affecting the performance of catalysts still remain controversially.…”
Section: Introductionmentioning
confidence: 99%
“…It is claimed that potassium promoter can enhance the activity of FTS [5] and water-gas shift reaction (WGS) [14], and increase the selectivity of the desired heavy hydrocarbons [15]. In addition, potassium promoter is known to promote CO adsorption and dissociation [16][17][18], improve (or suppress) H 2 adsorption [19][20][21], increase the carburization rate of iron catalysts [3], and suppress CH 4 formation [22]. Recently, K 2 O promotion has been proposed to modify the Fe crystallite morphology in stabilizing the more active facets [23].…”
Section: Introductionmentioning
confidence: 99%